KECEMASAN MENGHADAPI MASA PENSIUN PADA PEGAWAI NEGERI SIPIL DAERAH ISTIMEWA YOGYAKARTA DITINJAU DARI PENERIMAAN DIRINYA - , VICKRY YUDHISTIRA K., Dra. Aisah Indati, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to determine the relationship between selfacceptance and anxiety towards employee retirement at the among civil servant in Daerah Istimewa Yogyakarta. Variable in this study is self-acceptance and anxiety retirement. The subjects were employees of the Directorate General of Taxes that exist in the province of Yogyakarta over the age of 50 years which amounts to 32 people. Data collection techniques using a scale, which consists of self-acceptance scale and anxiety scales for retirement. The analysis technique used is the statistical method of product moment correlation coefficient Pearson. The final conclusion is that there is a negative relationship (rxy = -0,587) between self-acceptance with employee retirement anxiety at Regional Office of Directorate General of Taxation (DGT) Special Region of Yogyakarta selfacceptance means that the higher self-acceptance among employee then the lower the retirement anxiety. Conversely the lower the self-acceptance, the higher the employee retirement anxiety. Self-acceptance variables contribute effectively to the concerns facing retirement amounted 34,5% and most of the study subjects had low self-acceptance in the category of anxiety and a tendency to face future retirees subjects also included in the medium category.